INTEGRASI KONSEP TABAYUN DALAM AL-QUR'AN DAN FALSAFAH BUDAYA BANJAR "BISA-BISA MAANDAK AWAK" SEBAGAI NILAI ETIKA SOSIAL DI ERA DIGITAL - Muhammad Arsyad; Noor Hasanah (TASHWIR, 2025)
Abstract: This article explores the integration of the Qur'anic concept of tabayyun with the Banjar philosophy "Bisa-Bisa Maandak Awak" as a foundation for social ethics in the digital era. The topic is chosen in response to the rising spread of unverified information that often leads to social conflict. Tabayyun, as a principle of prudence in Islam, aligns with Banjar local wisdom that emphasizes self-control and social harmony. This study employs a qualitative method using library research, thematic Qur'anic interpretation, and cultural analysis. Primary data include Q.S. al-Ḥujurāt [49]:6 and literature on Banjar philosophy. The findings reveal a strong alignment between Qur'anic values and local traditions in shaping a media-literate, ethical society. This integration creates a contextual and Islamic-based model of digital social ethics. The result is significant for developing culturally grounded da'wah and character education as a strategy to promote religious moderation and social resilience. Keywords : Banjar Culture, Digital Era, Social Ethics, Tabayyun.